Sistem Informasi Manajemen, efek Transformasi Digital Madrasah Aliyah Al-Wathoniyah 5: Menggali Efektivitas SIM dalam Meningkatkan Kinerja Akademik dan Manajemen: Digital Transformation of Madrasah Aliyah: Evaluation of the Effectiveness of Management Information Systems in Improving Academic Performance and Management - Mania, Majidah Aqifah; Giu, Isra Yanuar; Nurpriatna, Ade (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This study aims to explore the effectiveness of the implementation of the Management Information System (MIS) at Madrasah Aliyah Al-Wathoniyah 5 East Jakarta in enhancing academic performance and school management. The research is grounded in the school's need to improve efficiency and transparency through digitalization since the MIS was introduced in 2020. A qualitative approach with a case study design was employed, involving observations, in-depth interviews, and document analysis. The key findings indicate that MIS has successfully improved efficiency in administrative management, strengthened transparency in financial and academic data management, and facilitated communication between the school, students, and parents. Technical challenges, such as suboptimal infrastructure, were addressed through collaboration with service providers and staff training. The implications of this study highlight the significant role of MIS in supporting the modernization and digitalization of the education system at the madrasah, while also revealing opportunities for further development to enhance educational quality.